Taxonomic revision of Schausiana Viette with two new species from Guatemala and notes on biogeography and correlated tectonics (Lepidoptera: Hepialidae) - Mielke, Carlos G.c.; Grehan, John R.; Monzón-Sierra, José (Zootaxa, 2020)
We morphologically validate the genus Schausiana Viette, 1950 as a monophyletic group comprising five species—S. phalerus (Druce, 1887) comb. n. and S. trojesa (Schaus, 1901) from Mexico, S. chalciope sp. n. and S. maishei sp. n. from Guatemala and S. pharus (Druce, 1887) comb. n. from Mexico to Costa Rica. Potential morphological monophyly of the genus is supported by the unique shared presence of specialized scales spine-like, elongate spinous, or piliform, located along the forewing veins. We investigate possible close phylogenetic relationships of this genus with the Mexican and Central American genera Pallas C. Mielke & Grehan, 2015, and Phassus Walker, 1856, and the southeastern Brazilian genus, Phthius C. Mielke & Grehan, 2017. Also discussed are the shared presence of several characters supporting the morphological monophyly of Schausiana, Phassus, and Pallas as ‘phassine’ Hepialidae. The distribution range of Schausiana is bounded in its northwestern range by the Guerrero terrane. Other than the widespread S. pharus with a disjunct record from Costa Rica, the southern distribution boundary corresponds to the Motagua-Polochic Fracture Zone in Guatemala. We suggest that the ancestral range of Schausiana did not include the Guerrero terrane and was possibly also absent from the Chocos Block (Honduras, El Salvador, Nicaragua) and the Costa Rica-Panama arc of Central America. Further divergence of Schausiana is predicted to have been influenced by tectonic events during late Cretaceous or early Cenozoic time. Colour photos are presented for all species for the first time. Holotypes of S. maishei, sp. n., and S. chalciope, sp. n., are deposited in the Universidad del Valle de Guatemala, Guatemala.